PENGARUH ELECTRONIC WORD OF MOUTH MELALUI APLIKASI TIKTOK TERHADAP MINAT BELI PADA PRODUK SKINTIFIC - Lita Liani Kintradinata; Riski Taufik Hidayah (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
eWOM is used as a marketing strategy used by many companies by utilizing social media. Skintific is a skincare brand that went viral on Tiktok in early 2022 and has become one of the brands discussed on TikTok. This study purpose to deeper understanding the effect of eWOM through the TikTok on buying interest in Skintific products. In understanding the influence of eWOM, this study applies an information adoption model (information quality, information quantity ,information credibility, information usefulness and information adoption). This research was conducted on a population of skincare users who see or like to look for references to Skintific skincare products on TikTok, so that a sample of 385 respondents was obtained using a purposive sampling technique which was collected through a questionnaire. SmartPLS SEM analysis was used to test the data in this study. The results state that the quality information, the quantity information and the credibility of information has an influence on the information usefulness, The information usefulness has an influence on information adoption and information adoption has an influence on purchase intention Skintific products.